Laporan Konsolidasi dan Laporan Keuangan Tersendiri Berdasarkan PSAK - Yuanne Gabrila Sriyanto; Pingky Nila Primasari; Endang Kartini Panggiarti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The consolidated financial report is a financial report that contains information on the financial condition and financial position of the operating activities of a parent company and one or more subsidiaries. Which is as if the company is a single company. Financial statements provided by parent companies (that is, investors controlling subsidiaries) and companies that reflect investments in subsidiaries, associates, and joint ventures at cost. PSAK 4 concerning Separate Financial Statements was approved by the Financial Accounting Standards Board on 19 December 2013. This PSAK 4 revises PSAK 4 concerning Consolidated Financial Statements and Separate Financial Statements which was issued on 22 December 2009.